Analisis Kemampuan Pemecahan Masalah Peserta Didik yang Belajar Dengan Strategi Problem Solving Berdasarkan Langkah Polya - Fajriah, Wina (Math Educa Journal, 2019)
The purpose of this study was to analyze the problem solving abilities of SMP Kartika I-6 grade VIII students, who learn with problem solving strategies based on Polya steps in solving story problems. This research is descriptive with a qualitative approach. The subject of this study was class VIII1 student. After  problem solving learning strategy are  applied, given test problem solving ability in participants and the results are analyzed based on the steps of pattern.Test results raising students in three levels of problem solving skills, namely a high level of 25 %, medium 50 %, lower 25%. Based on the indicator of problem solving, it is known that the ability of students in understanding problems and arranging settlement plans is in the high category, while in implementing the completion plan it is categorized as being moderate and checking the answers back at a low level.